Pathogenetic risk factors causing acute laryngotracheitis - Shakhnoza, Abdukodirova (Journal of Science in Medicine and Life, 2024)
Laryngotracheitis is a complex lesion of the respiratory tract, an acute or chronic disease of the respiratory tract. The pathological process is characterized by inflammation of the trachea and larynx, combined with injury. The disease is infectious in nature. Depending on the clinical condition, it is caused by bacteria, viruses or several agents at the same time (in this case, the pathological condition is slightly more severe). Violation is dangerous for health, and in some cases for the patient's life. It is fraught with many complications. Therefore, the disease cannot be ignored. Diagnosis and treatment of the pathological process, laryngotracheitis, the work of an otorhinolaryngologist. Conservative therapy is carried out. Usually outpatient. In rare cases, surgical treatment is required, but this is an extreme and very small measure of helping the disease.